The effects of hydroalcoholic extract of Allium elburzense Wendelbo bulb on dexamethasone-induced dyslipidemia, hyperglycemia, and oxidative stress in rats - Safaeian, Leila (Res Pharm Sci, 2018)
Recent evidences have suggested the beneficial cardiovascular effects of some plants belonging to the genus Allium. The present study is an attempt to investigate the effects of hydroalcoholic extract of Allium elburzense bulb on dexamethasone-induced dyslipidemia in rats. Total phenolic content of A. elburzense bulb hydroalcoholic extract was determined using Folin-Ciocalteu method. Thirty-six male Wistar albino rats in 6 groups were studied. Group 1 (dyslipidemic control) received dexamethasone (10 mg/kg/day, s.c.) for 7 days, groups 2-4 (treated) received dexamethasone and simultaneously treated orally with 100, 200, or 400 mg/kg of A. elburzense extract, group 5 (normal control) received a single daily injection of normal saline (1 mL/kg, s.c.) and the vehicle orally, and group 6 (reference) received dexamethasone and atorvastatin (40 mg/kg) orally. At the end of experiment, blood glucose, lipid profile, and malondialdehyde (MDA) levels were assessed in serum samples. Livers were processed for histopathological examination. Total phenolic content of A. elburzense extract was estimated to be 33.52 ± 1.3% mg gallic acid equivalent/g of the dried plant extract. The plant extract significantly reduced serum blood glucose, triglyceride, total cholesterol, low-density lipoprotein-cholesterol, and MDA levels and increased the high density lipoprotein-cholesterol level and also improved liver steatosis compared to the dyslipidemic control group. These results suggest the hydroalcoholic extract of A. elburzense bulb has anti-dyslipidemic, anti-hyperglycemic, and antioxidant effects on rats receiving high doses of dexamethasone.